High-Fat Diet Induced Perturbation in Physiological Parameters in Females Albino Rat - Saad, Basma M.; Abdelrazek, Heba M.A.; Shebl, Noha E.; Mansour, Samira R. (Journal of Advanced Veterinary Research, 2024)
A high-fat diet (HFD) is characterized by an excessive intake of dietary fats, while often being deficient in essential nutrients and fiber. Studies in animal models have consistently demonstrated that high-fat diets can lead to significant elevation of weight gain, body organs and biochemical parameters. The present research aimed to clarify the adverse physiological consequences of HFD on female rats. The present study was performed on 12 female rats that were divided to equal groups. Group I fed normal basal diet and group II fed HFD for 12 months. The body weight and gain, relative organs weight as well as abdominal fat mass were recorded. Hematological parameters, lipid profile, liver and kidney functions and Heart fatty acid binding protein (H-FABP) were determined. Also, histopathology for liver, kidney and heart were performed. Electrocardiography (ECG) was performed. The body weight, weight gain, relative organs weight and abdominal fat mass were significantly increased in group II than group I. Hematological parameters, lipid profile, liver and kidney functions, H-FABP and ECG as well as histopathology were deteriorated in group II than group I. The findings revealed that prolonged consumption of a high-fat diet resulted in significant physiological perturbations. Understanding the intricate interactions between high-fat diets, body weight, body organs and biochemical parameters is essential for devising effective prevention and treatment strategies for obesity and related metabolic disorders.